2020
DOI: 10.3390/biom10020222
|View full text |Cite
|
Sign up to set email alerts
|

CLytA-DAAO, Free and Immobilized in Magnetic Nanoparticles, Induces Cell Death in Human Cancer Cells

Abstract: D-amino acid oxidase (DAAO) catalyzes the oxidation of D-amino acids generating hydrogen peroxide, a potential producer of reactive oxygen species. In this study, we used a CLytA-DAAO chimera, both free and bound to magnetic nanoparticles, against colon carcinoma, pancreatic adenocarcinoma, and glioblastoma cell lines. We found that the enzyme induces cell death in most of the cell lines tested and its efficiency increases significantly when it is immobilized in nanoparticles. We also tested this enzyme therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…However, immobilization in GNPs and in alginate capsules significantly decreased the cell death induced by the treatment ( Figure 1 A), suggesting that these methods of CLytA-DAAO immobilization are less effective stabilizing the chimeric enzyme than MNPs. We had previously shown that the CLytA-DAAO-bound to MNPs together with D-Ala treatment induces a higher percentage of cells in subG1 phase than the free enzyme in several pancreatic carcinoma, colorectal carcinoma, and glioblastoma cell lines [ 11 ]. Here, a series of cell viability analyses were performed to confirm that, in fact, CLytA-DAAO bound to MNPs induced a significantly higher percentage of cell death compared to the free enzyme in all cancer models tested.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, immobilization in GNPs and in alginate capsules significantly decreased the cell death induced by the treatment ( Figure 1 A), suggesting that these methods of CLytA-DAAO immobilization are less effective stabilizing the chimeric enzyme than MNPs. We had previously shown that the CLytA-DAAO-bound to MNPs together with D-Ala treatment induces a higher percentage of cells in subG1 phase than the free enzyme in several pancreatic carcinoma, colorectal carcinoma, and glioblastoma cell lines [ 11 ]. Here, a series of cell viability analyses were performed to confirm that, in fact, CLytA-DAAO bound to MNPs induced a significantly higher percentage of cell death compared to the free enzyme in all cancer models tested.…”
Section: Resultsmentioning
confidence: 99%
“…The differences observed between free and immobilized in MNPs enzyme in viability ( Figure 1 A,B) and cell cycle analysis [ 11 ], were more pronounced than those observed in the MTT assays in pancreatic and colorectal carcinoma cell lines. The viability and cell cycle studies were conducted after 24 h treatment, whereas the MTT assays were carried out after 72 h treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations